Antibacterial activity of acalypha indica extract / Mastura Md Khalid - Md Khalid, Mastura (2014)
Number of resistant antibiotics is increasing and antibacterial activity testing is one of the steps to find treatment of diseases. Acalypha indica is well known medicinal plant and it a wild plant. It was used as infection treatment for generation to treat several diseases such as asthma, and pneumonia. A study on the antibacterial activity of this plant extract with different solvent used to support the therapeutic claims. The extract was prepared through maceration of dried powdered leaves and roots using methanol and water. It was tested with three different concentrations which were 70, 90 and 110 mg/ml. The streptomycin 10|ng was served as positive control while distilled water was used as negative control. Both extracted was tested on two gram positive bacteria (S. aureus and B.subtilis) and two gram negative bacteria {E.coli and P. aeruginosa) by using disc diffusion method. The results show that less antibacterial activity on both part of plant extract and extract with two different solvent due to insufficient or too low concentration. The mutant E.coli gene is one of other factor that affects the antibacterial activity result